EFEKTIVITAS DAN KONTRIBUSI PAJAK DAERAH KABUPATEN GORONTALO TAHUN 2017-2021 - Gobel, Yulia Puspitasari (CV. Kalimasada Group, 2023)
This study analyzes the Effectiveness of Regional Taxes of Gorontalo Regency and the Contribution of Local Taxes ofGorontalo Regency to Regional Original Income. This study uses a secondary data Quantitative descriptive method in theform of a Report on Realization of the 2017-2021 Regional Tax Revenue Budget for Gorontalo Regency. The results of theanalysis of regional tax effectiveness in Gorontalo Regency show that the results of measuring the effectiveness of local taxes arevery good with a large percentage of 100%, namely in 2017 it was 123%, in 2018 it was 126% and in 2019 it was121%, while the measurement of tax effectiveness in 2020 is the effectiveness of local taxes is less effective with a percentage of60% -80% with a yield of 75%, then the value of the effectiveness of local taxes in 2021 is not good with a percentage of<60% with a yield of 59%. In the analysis of the local tax contribution to regional own-source revenue that has been carriedout, it can be seen that in 2017 it was 11%, in 2018 it was 15% and in 2019 it was 20% with a percentage value between10.10% - 20% which shows that the contribution is less but experiencing an increase in 2020 of 24% and in 2021 of 23%indicates a moderate contribution of local taxes to PAD.